2018
DOI: 10.1037/cap0000128
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking the concept of learning disability.

Abstract: Learning disabilities are assumed to result from a neurological disorder that makes it very difficult for children to perform well in school. The unstated assumption is that there is a discontinuity in the distribution in aptitude for academic studies such that these children can be objectively categorised as having a learning disability or not. This assumption is based on an analogy with medical diseases or disorders in which certain tests can indicate whether or not a disease is present. However, this analog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Years later, a review by Butler et al. (2001) examined the benefits of teaching mathematics through peer tutoring involving students with learning disabilities, that is, students who have neurological differences in various mental processes that make it difficult for them to acquire certain skills, mostly in reading and mathematics (Penney, 2018). From a qualitative analysis, Butler et al.…”
Section: Introductionmentioning
confidence: 99%
“…Years later, a review by Butler et al. (2001) examined the benefits of teaching mathematics through peer tutoring involving students with learning disabilities, that is, students who have neurological differences in various mental processes that make it difficult for them to acquire certain skills, mostly in reading and mathematics (Penney, 2018). From a qualitative analysis, Butler et al.…”
Section: Introductionmentioning
confidence: 99%
“…From a qualitative perspective, Davidson concluded that the helping behavior that took place during peer tutoring was highly beneficial for the students academically and socially. Years later, a review by Butler et al (2001) examined the benefits of teaching mathematics through peer tutoring involving students with learning disabilities, that is, students who have neurological differences in various mental processes that make it difficult for them to acquire certain skills, mostly in reading and mathematics (Penney, 2018). From a qualitative analysis, Butler et al (2001) concluded that students with learning disabilities employed cognitive strategies successfully when peer tutoring was implemented.…”
Section: Introductionmentioning
confidence: 99%